Democratic Republic of São Tomé and Príncipe : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
São Tomé and Príncipe is classified as being in debt distress according to this joint World Bank-IMF low-income country debt sustainability analysis (DSA). This assessment has changed from the previous DSA completed in December 2017 (high risk of external debt distress) due to the prolonged negotiations on rescheduling external arrears. Nonetheless, São Tomé and Príncipe’s debt ratios have improved since the previous DSA. Specifically, the ratio of the present value of public and publicly-guaranteed (PPG) external debt to gross domestic product (GDP) no longer exceeds its threshold under the baseline scenario, due to lower-than-expected loan disbursements in 2017, an appreciation of the euro vis-à-vis the U.S. dollar, and higher-than-expected GDP deflator growth. As in the previous DSA, the debt service ratios stay below their respective thresholds under almost all scenarios. Nevertheless, the ratios of the present value of debt to exports and to revenue still exceed their respective thresholds under the baseline scenario early in the projection period, though they decline over time. This DSA underscores the importance of lowering all PPG external debt indicators below their thresholds by continuing fiscal consolidation, eschewing non-concessional loans, promoting growth, and expanding the export base.